Kejadian Streptococcus suis pada Babi yang Dipotong di Rumah Pemotongan Hewan untuk Babi di Denpasar - Besung, I Nengah Kerta; Agustina, Kadek Karang; Suarjana, I Gusti Ketut; Suwiti, Ni Ketut; Mahardika, I Gusti Ngurah Kade (Jurnal Veteriner, 2022)
Streptococcosis cause by Streptococcus suis is an important bacterial disease because it has zoonotic potential and is capable of causing serious outbreaks in both pigs and humans. The main symptoms are meningitis, deafness, inflammation of the eyes to blindness. This study aims to find the presence of S. suis bacteria infection on slaughtered pigs in Denpasar. A total of 200 pig tonsils were taken as samples with 20 sampling times. Each sampling was taken 10 samples. The samples were grown on 5% sheep blood agar then followed by Gram staining, oxidase, coagulase, and catalase test. Suspected positive results in each collection were continued with the Polymerase Chain Reaction primers SSRecN-F and SSRecN-R tests. The results of testing on 200 samples of pig tonsils showed that 2.5% of samples were positive for S. suis. Based on the results of the study, it can be concluded that the sample of pig tonsils from the pig slaughterhouse in Denpasar was infected with S. suis.